Mediterranean Sea: A Failure of the European Fisheries Management System - Cardinale, Massimiliano; Osio, Giacomo Chato; Scarcella, Giuseppe (Frontiers in Marine Science, 2017)
North East Atlantic and the Mediterranean Sea fisheries are governed by the European Common Fisheries Policy (CFP). Despite the fact that both areas are managed under the same broad fishery management system, a large discrepancy in management performance occurs, with recent considerable improvement of stock status witnessed in the North East Atlantic and a rapidly deteriorating situation in the Mediterranean Sea. The control of fishing effort combined with specific technical measures, such as gear regulation, establishment of a minimum conservation reference size and selective closure of areas and seasons, is the main management strategy adopted by Mediterranean Sea EU countries. On the other hand TAC (Total Allowable Catches) is the major regulatory mechanisms in the North East Atlantic. Here we analysed all available stock assessment and effort data for the most important commercial species and fleets in the Mediterranean Sea since 2003. The analysis shows that there is no apparent relationship between nominal effort and fishing mortality for all species. Fishing mortality has remained stable during the last decade, for most species, with a significant decline observed only for red mullet and giant red shrimp but an increase for sardine stocks. Also, current F is larger or much larger than FMSY for all species. Despite catch advice are produced by STECF each year, the realised catches have usually been much larger than the scientific advice. A recent analysis argued that this dichotomy might be due to several factors, such as the better enforcement of monitoring control and surveillance in North East Atlantic, the more complex socio-economic situation and the less effective management governance in the Mediterranean Sea. Here we argue instead that major reasons for the alarming situation of Mediterranean Sea stocks can be found in the ineffectiveness of the current effort system to control F, the continuous non-adherence to the scientific advice and inadequacies of existing national management plans as a key management measure. It is therefore undoubted that alternatives management measures as a TAC based system are necessary if Europe is willing to achieve the objectives of the CFP before 2020 in the Mediterranean Sea.